Study of reduction of nickel (II) compounds by complex solid reducing agent - Лобойко, Вячеслав Алексеевич; Бутенко, Анатолий Николаевич; Юрченко, Анна Александровна; Довбий, Татьяна Анатольевна; Лавренко, Антонина Александровна (Eastern-European Journal of Enterprise Technologies, 2013)
The article discusses the method of the chemical reduction, namely the use of hexamine for the reduction of compounds of nickel (II), namely, nickel (II) hydroxide. The main objective of the study is to determine the optimal process parameters (temperature and time of reduction), with the prospect of the introduction of the proposed method in the industry. The comparative analysis of currently used solid reducing agents indicates the benefit of hexamine application. The use of modern instrumental methods of analysis permits to carry out the analytical control over the completeness of reduction of Ni (OH) 2. The described in this paper thermographic studies permit to obtain technologically weighty information that is important to choose the best way of the chemical reduction of compounds of nickel (II) to metallic powder. The results can be used by experts working in the field of inorganic synthesis, as well as in the field of production of metals from secondary raw materials. The established process parameters allow the optimization of this process, not only from a technological point of view, but also from the economic.